2020
DOI: 10.3390/plants9070868
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Reporters for Visualizing Alternative Splicing of Hormonal Genes

Abstract: Rapid progress in plant molecular biology in recent years has uncovered the main players in hormonal pathways and characterized transcriptomic networks associated with hormonal response. However, the role of RNA processing, in particular alternative splicing (AS), remains largely unexplored. Here, using example genes involved in cytokinin signaling, brassinosteroid synthesis and auxin transport, we present a set of reporters devised to visualize their AS events in vivo. These reporters show a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Moreover, PIN7a and PIN7b form homo- and heterodimers and show the rates of lateral mobility dropping closer to intermediate values when co-expressed (Figure 2b). Consistently, PIN7b reverts the exaggerated tropic response conferred by PIN7a , phenocopying that of the wild-type PIN7 allele (Kashkan et al, 2020; 2021).…”
Section: Mutually Dependent Subcellular Distributionmentioning
confidence: 67%
“…Moreover, PIN7a and PIN7b form homo- and heterodimers and show the rates of lateral mobility dropping closer to intermediate values when co-expressed (Figure 2b). Consistently, PIN7b reverts the exaggerated tropic response conferred by PIN7a , phenocopying that of the wild-type PIN7 allele (Kashkan et al, 2020; 2021).…”
Section: Mutually Dependent Subcellular Distributionmentioning
confidence: 67%
“…However, this may not describe the actual situation at the resolution of individual cells. To address this, we analyzed the P7A 1 G and P7BR fluorescent reporters (Kashkan et al ., 2020), which allow for monitoring the activity of the AS of PIN7 in planta and in situ (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…3a,b), and it seems that the subtle defects resulting from disruption of the single PIN3 ‐clade genes are more pronounced under specific environmental cues (Adamowski & Friml, 2015; Ogura et al ., 2019), where joint AS of PIN7 and PIN4 may play a role. Although publicly available transcriptomic resources do not indicate that expression of the individual PIN7 or PIN4 isoforms is dramatically changed under a wide range of experimental conditions (Martín et al ., 2021), we observed that expression of PIN7a could be lowered by the application of exogenous auxin (Kashkan et al ., 2020). Given that disabling several factors involved in AS leads to auxin‐related defects (Kalyna et al ., 2003; Casson et al ., 2009; Retzer et al ., 2014; Hrtyan et al ., 2015; Tsugeki et al ., 2015; Bazin et al ., 2018), this mode of regulation of AS of PIN7 (and PIN4 ) suggests the existence of an unknown auxin‐mediated pathway, active at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may not describe the actual situation at the resolution of individual cells. To address this, we analyzed the P7A 1 G and P7BR fluorescent reporters (Kashkan et al, 2020), which allow for monitoring the activity of the AS of PIN7 in planta and in situ (Figure 2A). Indeed, in most cells, including the primary root tip (Figure 2B) or in the hypocotyl during the light bending assay (Figure 2C), we observed generally overlapping expression of both isoforms without any apparent tissue preference.…”
Section: Fluorescent Reporters Reveal Highly Overlapping Pin7a and B Expressionmentioning
confidence: 99%